The Application of The Project Based Learning Model in Improving Writing Skills in Class IV State SD 107402 Saentis Academic Year 2021/2022 - Kumala Sari Dalimunthe, Jamilah (Journal of General Education Science, 2022)
The object of this research is the writing skills of fourth grade students at SD Negeri 107402 Saentis. This research was conducted from July 2022 to September 2022. The data analysis techniques in this study consisted of four stages: (1) planning, (2) implementing, (3) observing, and (4) reflecting on class action. The results of this study indicate that the application of the Project-Based Learning Model can improve the Writing Skills of Grade IV Students at SD Negeri 107402 Saentis for the 2021/2022 Academic Year. This improvement is shown by the quality of the learning process which is reflected in the activeness of students during learning, the attention and improvement of students' writing skills, students' interest during learning and students' courage in presenting their writing in front of the class. Then the researchers continued the research until cycle III increased, namely in cycle I it was only 75.00% to 83.33% in cycle III and was included in the good category with an average value of 80.81. Because it has reached the completeness criteria, namely 80% of students scored more than or equal to the KKM (70), this study was said to be successful. Then the researchers continued the research until cycle III increased, namely in cycle I it was only 75.00% to 83.33% in cycle III and was included in the good category with an average value of 80.81. Because it has reached the completeness criteria, namely 80% of students scored more than or equal to the KKM (70), this study was said to be successful.